2018
DOI: 10.1051/matecconf/201824511004
|View full text |Cite
|
Sign up to set email alerts
|

New fire retardant compositions for fire-resistant automatic curtains

Abstract: The paper overviews the way by which intumescent fire retardant compositions act as fillers in fire-resistant automatic curtains. A several intumescent compositions, which form a heat-isolating charred layer when they are exposed to high temperatures, were produced and applied to the mineral-fabric basis of the curtain. Fire-protective properties of produced materials were assessed and compared with foreign specimens. Swelling coefficient and material’s fire durability were considered as operating parameters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In this formulation, the definition also contains information about the composition of the concept of "fire protection means", indicating that it refers to fire retardants, compositions and materials. In turn, fire retardants are subdivided into fire retardant varnishes and paints, impregnating compounds, greases and pastes, and combined compositions [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…In this formulation, the definition also contains information about the composition of the concept of "fire protection means", indicating that it refers to fire retardants, compositions and materials. In turn, fire retardants are subdivided into fire retardant varnishes and paints, impregnating compounds, greases and pastes, and combined compositions [12][13][14][15].…”
Section: Methodsmentioning
confidence: 99%
“…Based on a patent search and analysis of scientific literature [28][29][30][31], eight samples were constructed, additionally containing in the first and last layer a silica heat-shrinkable fabric KT-E-115-TO (Table 2), This means that Sample No. 1 was composed of heat-shrinkable fabric + intumescent composition + heat-shrinkable fabric.…”
Section: Determination Of the Compositions Of The Fabric Layers Of A ...mentioning
confidence: 99%
“…On the other hand, many studies have focused on using additions of expanding materials, which can expand because of heating and endothermic processes, to develop fireresistant curtains. Such materials include vermiculite, perlite, and oxidized graphite [29]. In another study, Anhui Jianzhu University has reported the satisfactory fireproof performance of recycling thermosetting polyurethane plastics, whose outer side of the board is a fireproof layer composed of nonwoven fabric and inorganic paste, and whose middle is rigid polyurethane foam [30].…”
Section: Perlite As Flame-retardant Filler For Textile Materialsmentioning
confidence: 99%